RESPONSE OF SOME COWPEA VARIETY (Vigna unguiculata) TO THE ALLELOPHATIC EFFECT OF Khaya senegalensis AND Eucalyptus camaldulensis - MOHAMMED, U. A.; DANJUMA, O.; SULEIMAN, K.; AISHA, B. M.; SAFWAN, I. I (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2021)
Availability of land for arable farming is a major concern with increase in population which leads to needs for more infrastructures and more farmers. Some of these fields used have economic trees with allelopathic effects. It is therefore important to understand this allelophatic effects and find a sustainable solution. The allelopathic inhibitory effects of leaf extracts of Khaya senegalensis and Eucalyptus camaldulensis were investigated on the preliminary growth of three Cowpea (Vigna unguiculata) genotypes; Aloka Aloka, IT99K-573-1-1 and IT99K-573- 2-1 at 3% and 5%. A randomized complete block design was employed in small plastic bags. Growth parameters such as shoot and root length, number of leaves, stem girth and leaf area index were determined. The study revealed that leaves extracts of Eucalyptus camaldulensis and Khaya senegalensis significantly (p < 0.05) affected the growth of the three cowpea genotypes, Aloka Aloka, IT99K-573-1-1 and IT99K-573-2-1 with increase in concentration. This clearly indicated the inhibitory properties the leaves extracts possess. The findings in this study indicated that IT99K-573-1-1 tolerated the inhibition more at 3% and 5% compared to the other genotypes. Farmer can plant this cowpea genotype, IT99K-573-1-1 close when they have Khaya senegalensis and Eucalyptus camaldulensis in or around there crop fields.